Design of Islamic Financial Certificates for Housing Development in Algeria - Tabet, Imene; Kahf, Monzer; Kahf, Monzer (INT ISLAMIC UNIV MALAYSIA, PRESS RESEARCH MANAGEMENT CENTER, 2018)
Algeria depends solely on publicly produced housing. Algeria's housing industry has been lagging behind in its development. This has caused many citizens to struggle with finding proper housing. Aside from being one of the highest countries in terms of rent rates. construction and distribution of public houses in Algeria takes more than 15 years of waiting. Despite that the quality of the housing is bad. This paper proposes Shari'ah-compliant housing certificates, a new Islamic financial instrument that would assist in house construction in Algeria. This instrument uses Istisna" as the underlying contract and accommodates guaranteed returns as well as negotiability for investors. It has great potential in contributing to solving the prolonged problem of housing in Algeria as well as countries facing problems in financing the construction of housing.
WOS: 000450537700010
Keywords: Housing certificates; Istisna'; Islamic Financial Instrument; Sukuk; Housing Development; Sukuk; Mudharabah